Genetic diversity in muskmelon based on SSR markers and morphological traits under well-watered and water-deficit condition. (July 2020) - Ansari, Waquar Akhter; Atri, Neelam; Yang, Luming; Singh, Bijendra; Pandey, Sudhakar
Abstract: In the present study genetic diversity among 48 muskmelon accessions was analyzed employing various morphological traits under well-watered and water-deficit condition and SSR markers. Maximum values for horticultural traits were, 44 cm for fruit polar circumference, 33.2 cm for fruit equatorial circumference, 21 for number of fruits, 41.5 for days to first male flowering, 44 for days to 50% male flowering, 44 days to first female flowering, 45 days to 50% female flowering and 5.66 for number of shoot branching under well-watered condition. While under water-deficit condition maximum values of same parameters were 28.8 cm, 26 cm, 18, 37.2, 39, 47, 46.2 and 4.4, respectively. Based on morphological traits genotypes were clustered in three major clusters under well-watered condition, while grouped in five major clusters under water-deficit condition. Out of the 52 SSR markers, 35 produced polymorphic patterns, a total of 125 amplification products were obtained, the mean number of alleles per locus was 3.57, and the size of amplified products ranged from 120 bp to 605 bp. The average PIC value was estimated to be 0.492. Jaccard similarity coefficients calculated from SSR data varied from 0.03 to 0.89 with a mean value of 0.46. The clustering pattern of muskmelon accessions based on SSR markers was random but not in consonance with the groupings based on quantitative traits under well-watered and water-deficit condition. High genetic variability was observed based on various morphological traits, under both well-watered and water-deficit condition and SSR markers, indicating genetically diverse accessions. Highlights: Muskmelon accessions genetic diversity based on morphological and molecular marker were assessed. Among the studied accessions great diversification observed based on morphological traits. Genetic diversity observed under both well-watered and water-deficit condition. Based on SSR marker accessions were grouped in seven major groups.